Ischemic preconditioning does not improve peak exercise capacity at sea level or simulated high altitude in trained male cyclists - Hittinger, E. A.; Maher, J. L.; Nash, M. S.; Perry, A. C.; Signorile, J. F.; Kressler, J.; Jacobs, K. A. (Applied Physiology, Nutrition, and Metabolism, 2015)
Ischemic preconditioning (IPC) may improve blood flow and oxygen delivery to tissues, including skeletal muscle, and has the potential to improve intense aerobic exercise performance, especially that which results in arterial hypoxemia. The aim of the study was to determine the effects of IPC of the legs on peak exercise capacity (Wpeak), submaximal and peak cardiovascular hemodynamics, and peripheral capillary oxygen saturation (SpO2) in trained males at sea level (SL) and simulated high altitude (HA; 13.3% FIO2, ~3650 m). Fifteen highly trained male cyclists and triathletes completed 2 Wpeak tests (SL and HA) and 4 experimental exercise trials (10 min at 55% altitude-specific Wpeak then increasing by 30 W every 2 min until exhaustion) with and without IPC. HA resulted in significant arterial hypoxemia during exercise compared with SL (73% ± 6% vs. 93% ± 4% SpO2, p < 0.001) that was associated with 21% lower Wpeak values. IPC did not significantly improve Wpeak at SL or HA. Additionally, IPC failed to improve cardiovascular hemodynamics or SpO2 during submaximal exercise or at Wpeak. In conclusion, IPC performed 45 min prior to exercise does not improve Wpeak or systemic oxygen delivery during submaximal or peak exercise at SL or HA. Future studies must examine the influence of IPC on local factors, such as working limb blood flow, oxygen delivery, and arteriovenous oxygen difference as well as whether the effectiveness of IPC is altered by the volume of muscle made ischemic, the timing prior to exercise, and high altitude acclimatization.